2017
DOI: 10.1080/09537104.2017.1293802
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical outcome of profound thrombocytopenia in adult patients with DENV infections

Abstract: Severe thrombocytopenia is common in dengue virus (DENV) infections. However, studies focusing on the role of profound thrombocytopenia (PT) (nadir platelet counts ≤ 20 000/mm) in DENV infections are scarce. This study aims to identify the associated features and outcome of DENV patients with PT. It involves 237 adult hospitalized patients who were DENV PCR positive. The presence of comorbidity (AOR = 4.625; 95% CI = 1.113-19.230), higher admission hematocrit (AOR = 1.213; 95% CI = 1.067-1.379), lower admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Bone marrow suppression and platelet destruction have been hypothesized as the cause of thrombocytopenia in DENV infections, with a rapid decrease in platelet counts constituting a WHO dengue warning sign [ 4 , 23 , 28 ]. Platelet levels generally show a dynamic decline, reaching a nadir by 3 to 6 days of fever onset [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow suppression and platelet destruction have been hypothesized as the cause of thrombocytopenia in DENV infections, with a rapid decrease in platelet counts constituting a WHO dengue warning sign [ 4 , 23 , 28 ]. Platelet levels generally show a dynamic decline, reaching a nadir by 3 to 6 days of fever onset [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Major haemorrhage referred to clinically significant bleeding requiring red cell transfusion whereas, minor haemorrhage referred to mucosal bleeding such as gum bleeding, nasal bleeding not requiring red cell transfusion [ 23 ]. Severe thrombocytopenia was defined as platelet count < 50,000/ mm 3 , a level shown to be associated with additional severe manifestations [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The clinical presentations of dengue fever range from a self-limited febrile illness to dengue hemorrhagic fever, characterized by plasma leakage, plasma concentration, and hypoalbuminemia and profound thrombocytopenia. 3…”
mentioning
confidence: 99%
“…Most clinical guidelines recommend platelet transfusion in patients with dengue who develop severe bleeding or platelet counts below 10-20,000/mm 3 . However, another study confirms that platelet transfusion does not prevent the development of severe bleeding or shorten coagulation time [55], and in severe dengue disease with hemorrhagic manifestations, the need for intensive care was not significantly associated with PT [52].…”
Section: Thrombocytopenia Induced By Bone Marrow Suppression Lysis Omentioning
confidence: 99%
“…The kinetic observation of platelet counts in dengue patients showed a mild to moderate decrease in the 3rd to the 7th day, a significant decrease on day 4, reaching normal levels in the 8th or 9th day of the disease [50,51]. Profound thrombocytopenia (nadir platelet count ≤20,000/mm 3 ) was significantly more likely to detect early warning signs and longer hospital stays, but profound thrombocytopenia was not affected by DENV serotypes, coinfections, and secondary DENV infections [52]. However, a study involving 245 dengue patients showed no relationship between bleeding and platelet count, while 81 nonbleeding patients had a score below 20,000/mm 3 [53].…”
Section: Thrombocytopenia Induced By Bone Marrow Suppression Lysis Omentioning
confidence: 99%